Kran Air Minum Galon Otomatis Berbasis Sensor Inframerah - Erman Al Hakim; Asrori, Guntur Firdous Asrory; Asni Tafrikhatin; Hamid Nasrullah; Jati Sumarah (Politeknik Piksi Ganesha Indonesia, 2023)
Usually people drink clean water from gallon dispensers to meet their daily needs. Furthermore, automatic drinking water dispensers are designed to facilitate the operation of automatic drinking water faucets by automatically filling drinking water without the need to press the gallon suction button. Based on these problems, the authors automatically produce drinking water faucets based on infrared sensors using the R&D (Research & Development) method, in particular by conducting research and developing the currently available tools. One gallon automatic drinking water faucet uses infrared sensor, electric motor or water pump, relay, faucet PCB, ribbon cable and female hook connector. The infrared sensor detects the glass marked with the LED signal light and the power LED turns green, then receives the signal sent to the switch relay to automate the operation of the water pump/electric motor to dispense gallons of water.